Flexible all-solid-state supercapacitors of polyaniline nanowire arrays deposited on electrospun carbon nanofibers decorated with MOFs. (28th December 2018) - Yao, Mengyao; Zhao, Xin; Zhang, Junxian; Tan, Wenjun; Luo, Jie; Dong, Jie; Zhang, Qinghua
Abstract: Porous carbons derived from metal–organic frameworks (MOFs) are promising materials for a number of energy- and environment-related applications. To integrate the powder MOFs-derived carbon into feasible engineered materials, a facile strategy to fabricate integrated flexible film is developed by growing MOFs nanoparticles on polyimide electrospun nanofibers, followed by calcination, to fabricate freestanding carbon nanofiber membranes decorated with porous carbon. Then vertically polyaniline nanowire arrays are uniformly deposited on the hierarchical porous carbon substrates by in situ polymerization. Thanks to the good distribution of MOFs-derived porous carbon on carbon nanofibers and the compact configuration interwoven by conducting polymers, the designed hybrid electrode could be used directly as a freestanding electrode for supercapacitors, which displayed a high specific capacitance of 1268 F g −1 . The assembled flexible solid-state supercapacitor based on the integrated electrodes demonstrated a high volumetric capacitance of 1973 mF cm −3 and a good capacitance retention of 84.9% after 10 000 cycles, which could power a commercial light emitting diode. This strategy may shed light on the design of MOFs-based flexible materials for practical applications of supercapacitors and other electrochemical devices.